Vascular endothelial growth factor-loaded poly(lactic-co-glycolic acid) microspheres-induced lateral axonal sprouting into the vein graft bridging two healthy nerves: Nerve graft prefabrication using controlled release system - AKAKIN, DİLEK; ALARÇİN, EMİNE; KERİMOĞLU, OYA (WILEY-BLACKWELL, 2012)
The most commonly used surgical technique for repairing segmental nerve defects is autogenous nerve grafting; however, this method causes donor site morbidity. In this study, we sought to produce prefabricated nerve grafts that can serve as a conduit instead of autologous nerve using a controlled release system created with vascular endothelial growth factor (VEGF)-loaded poly(lactic-co-glycolic acid) (PLGA) microspheres. The study was performed in vitro and in vivo. For the in vitro studies, VEGF-loaded PLGA microspheres were prepared. Thirty rats were used for the in vivo studies. Vein grafts were sutured between the tibial and peroneal nerves in all animals. Three groups were created, and an epineural window, partial incision, and microsphere application were performed, respectively. Walking track analysis, morphologic, and electron microscopic assessment were performed at the end of the eight weeks. Microspheres were produced in spherical shapes as required. Controlled release of VEGF was achieved during a 30-days period. Although signs of nerve injury occurred initially in the partial incision groups according to the indexes of peroneal and tibial function, it improved gradually. The index values were not affected in the other groups. There were many myelinated fibers with large diameters in the partial incision and controlled release groups, while a few myelinated fibers that passed through vein graft in the epineural window group. Thereby, prefabrication was carried out for the second and third groups. It was demonstrated that nerve graft can be prefabricated by the controlled delivery of VEGF. (c) 2012 Wiley Periodicals, Inc. Microsurgery, 2012.
Keywords: TO-SIDE NEURORRHAPHY; EPINEURIAL SHEATH; GENE-THERAPY; REGENERATION; REPAIR; CONDUITS; DEFECTS; RECONSTRUCTION; ENHANCEMENT; RATS